SEORANG PENDERITA DENGAN LEUKEMIA MIELOID KRONIK DAN MIELOMA MULTIPEL - Suega, Ketut (journal of internal medicine, 2010)
Chronic Myeloid Leukemia (CML) and Multiple Myeloma (MM) are two chronic progressive diseases characterizedby neoplastic proliferation of myeloid cell and monoclonal plasma cell. Chronic myeloid leukemia was recognized as a distinctentity, associated with massive splenomegaly and as ! rst malignant disease found to be constitutively associated with spesi! ccytogenetic abnormality the Philadelphia oncogene. Whereas MM is frequently recognized by monoclonal protein productionand either difuse osteoporosis or lytic bone lesion. Clinical manifestation are consequence of marrow in! ltration of plasma cells,production of M protein in blood or urine and immune de! ciency. Coincidence of these two diseases in one particular patient is avery rare occasion. Herewith we reported a woman 42 years old Balinese presented of abdominal enlargement without symptomof bone pain, anemic syndrome. After complete examination supporting by ! nding on bone marrow examination this patient! nally diagnosed of having chronic phase of CML and MM stage IIIB as well. Treatment was given with hydroxy urea andother supported measures and we planned to continue with melphalan and prednisone. There were no clear explanation for thiscondition whether it occur concomitantly or one disease follow with the other. Several reports found that in quite similar occasionMelphalan was the agent of suspected with induced secondary malignancy. Others also found twenty MDS patient togetherwith lymphoid malignancy and plasma cell. Tanaka et.al., noted that a more satisfactory explanation is that both disorders arefrom malignant transformation of a precursor cell capable of differentiating into both lymphoid and myeloid lines. In our casemore likely that CML concomitantly found with MM because there were no previous history of having chemotherapy norradiotherapy.